2019
DOI: 10.1039/c9cp02126d
|View full text |Cite
|
Sign up to set email alerts
|

PET and FRET utility of an amino acid pair: tryptophan and 4-cyanotryptophan

Abstract: The amino acids tryptophan and 4-cyanotryptophan constitute a dual FRET and PET pair, useful for various biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Bearing this in mind, an original approach for l -Trp@Ti 3 C 2 T x was devised in order to exploit the two molecular properties offered by the aromatic core in l -Trp. In particular, Förster resonance energy transfer (FRET) phenomenon , was considered for the evaluation of the supramolecular interactions and fluorescence all at once (Figure a). Briefly, the process of FRET takes place when a fluorophore in an electronically excited state (donor) transfers its excitation energy to a nearby chromophore (acceptor).…”
Section: Resultsmentioning
confidence: 99%
“…Bearing this in mind, an original approach for l -Trp@Ti 3 C 2 T x was devised in order to exploit the two molecular properties offered by the aromatic core in l -Trp. In particular, Förster resonance energy transfer (FRET) phenomenon , was considered for the evaluation of the supramolecular interactions and fluorescence all at once (Figure a). Briefly, the process of FRET takes place when a fluorophore in an electronically excited state (donor) transfers its excitation energy to a nearby chromophore (acceptor).…”
Section: Resultsmentioning
confidence: 99%
“…RaPID selections for de novo cyclic peptides initiated with ClAc−4CNW or ClAc−AzAla will enable the identification of peptide leads that are inherently fluorescent and can be directly assessed for cell permeability by fluorescence microscopy and flow cytometry. 4CNW and AzAla have also recently been used to probe protein‐protein binding interactions by PET, FRET and VET [9,17,18] . We therefore also envisage that 4CNW/AzAla initiated peptide leads could be used directly in label‐free binding assays.…”
Section: Methodsmentioning
confidence: 99%
“…4CNW and AzAla have also recently been used to probe protein‐protein binding interactions by PET, FRET and VET. [ 9 , 17 , 18 ] We therefore also envisage that 4CNW/AzAla initiated peptide leads could be used directly in label‐free binding assays.…”
mentioning
confidence: 99%
“…Besides its utility in biological microscopy, 4CN-Trp can also be used in various spectroscopic applications. For example, the study of Ahmed et al demonstrated that Trp can effectively quench the fluorescence of 4CN-Trp via the mechanism of photoinduced electron transfer (PET). Since this quenching process only becomes efficient when the indole and 4CN-indole rings are sufficiently close (i.e., in van der Waals contact), this fluorophore–quencher pair can be used to assess protein conformational dynamics via either ensemble or single-molecule fluorescence techniques.…”
Section: Emerging Visible Fluorescent Amino Acidsmentioning
confidence: 99%